A bibliometric analysis of paramedicine publications using the Scopus database: 2010–2019. (November 2021) - Beovich, Bronwyn; Olaussen, Alexander; Williams, Brett
Highlights: Paramedicine is an emerging profession which is developing a unique knowledge base. Bibliometric analysis is a valuable tool to examine the paramedicine literature. Paramedicine research publication has progressively increased over the last decade. There is a relative lack of paramedic authors and publications in top journals. Ongoing development of scholarly activity in paramedicine is required. Abstract: Background: Paramedicine is an evolving profession undergoing increases in scholarly activity and peer-reviewed publications. This study aims to complete the first extensive bibliometric examination of the worldwide paramedicine literature. Method: Scopus was utilised to search for paramedicine-based articles published in peer-reviewed journals between 2010 and 2019 inclusive. The included articles were examined for citation count, journal, journal quartile, country of origin, university affiliation, collaboration, and topic. Results: Paramedicine-based publications have steadily increased and are predominantly published in prehospital or emergency healthcare journals. The majority of highly cited authors were located in Australia; however, only one of these authors was identified as a paramedic. Monash University (Australia) was the most productive institution (11.7% of total articles) and collaboration was mostly within national boundaries (53.2%). Conclusion: This study demonstrates the progressive increase in paramedic scholarly activity over the past decade. Although a large number of articles originate from two countries (Australia and the USA) and one university, numerous nations and institutions are contributing to this body of knowledge. The growing literature base is indicative of the evolution of paramedicine; however, the high level of non-paramedic authors suggests the opportunity for further scholarly development within the paramedic discipline.